Love, Rosie [S láskou Rosie po anglicky] - Ahern, Cecelia, 1981- (Harper, 2014)
Best friends since forever, Rosie and Alex have shared their hopes, dreams, awkward moments - and firsts. But their bond is threatened when Alex's family move to America. They stay in touch, but misunderstandings, circumstances and sheer bad luck seem to be conspiring to keep them apart. Can they gamble everything - even their friendship - on true love?